Relationship between talent management practices and employee retention / Mohd Najmuddin Md Ali - Md Ali, Mohd Najmuddin (Faculty of Business and Management, 2019)
The research objective is to examine whether talent management practices which include career development, rewards and compensation, performance management and job design have a positive relationship on employee retention. The target respondents in this study are employees who work in manufacturing industries in Taman Perindustrian which include SIS Speedy, Happy Grass Sdn Bhd and Greenfarm Food Industries Sdn Bhd. The collected data will be analyze using Statistical Package for Social Science (SPSS) software. Descriptive analysis, reliability test, Pearson Correlation Analysis and Multiple Regression will be used to analyze the collected data. The study revealed that there are positive effects towards employee retention given from the talent management practices which include career development, rewards and compensation and performance management. The result of this study will be useful to manager and human resources in an organization to have deeper understanding how talent management influenced in employee retention. It allowed the organization to be able to implement policy, remuneration or plan to retain their talented employee.